The determinants affecting retention among employee of KPJ Bandar Maharani Specialist Hospital / Farah Hani Hassim - Hassim, Farah Hani (Faculty of Business and Management, 2017)
Employee retention has been one of critical issues faced by the employer in the country. Moreover, it is costly for the organization to lose manpower with great talent who left the organization as it involves the cost of hiring, training and the loss of quality and productivity with the new employee. Therefore, this study aims to investigate the determinants of retention among employees of KPJ Bandar Maharani Specialist Hospital. This research was aimed to achieve the following objectives: identify the determinants affect employee retention; investigate how job satisfaction affects retention among employees at KPJ MSH ; study the relationship between organization commitment and employee retention in KPJ MSH ; determine how leadership role can affect the KPJ MSH’s employees retention ; and identify the major factor of retention among the employees of KPJ MSH. The total population of the research is 173 employees of KPJ MSH with sample size 107 respondents. Disproportionate stratified random sampling has been used as sampling technique for this research. A self-developed questionnaire, measured on Likert scale was used to collect data from respondents. The questionnaire had Cronbach alpha of a= 0.873 which shown the instrument is reliable. Moreover, the results have shown that job satisfaction, organization commitment and leadership role has a positive and significant relationship with employee retention. Therefore, the result will help the company to increase the employees’ satisfaction and commitment in order to retain the employee.